SELF-DUAL KERR-SCHILD METRICS AND NULL MAXWELL FIELDS - Tod, K (1982)
A construction for self-dual solutions of Einstein's equations with metric in Kerr-Schild form from null electromagnetic fields in Minkowski space is described. Two examples are given. © 1982 American Institute of Physics.